Lifestyle changes, mental health, and health-related quality of life in children aged 6-7 years before and during the COVID-19 pandemic in South Germany - Deborah Kurz; Stefanie Braig; Jon Genuneit; Dietrich Rothenbacher (BMC, 2022)
Abstract Background The measures against the COVID-19 pandemic are challenging for children and parents, and detrimental effects on child health are suggested especially from lock-down measures and school closings. Methods We conducted a cross-sectional analysis using a population based longitudinal (birth-) cohort study (SPATZ study) conducted in the South of Germany. Data included all 6 or 7 year old children for whom a questionnaire was completed during first grade of school. Consequently, we were able to analyze children being in first grade before the first lockdown in Germany (≤ 15th March 2020), as well as children being in first grade during the pandemic (> 15th March 2020). We conducted descriptive statistics and estimated the associations between the two time periods, before and during the pandemic, and various outcomes of child health using multivariable adjusted linear or logistic regression modeling. The analysis was stratified by gender. Results Results among n = 362 children aged six or seven years showed substantially lower mean scores of health-related quality of life (difference in means: − 5.5, 95% confidence interval (CI) − 9.0, − 2.0), and higher mean scores in total emotional and behavioral difficulties (difference in means: 2.0, 95% CI 0.2, 3.8) in girls during vs. before the COVID-19 pandemic using multivariable linear regression modeling. In addition, weekly screen-time was increased in boys by 3.5 h (95% CI 0.6, 6.4). We did not find substantial differences in sleep quality, physical activity, and time spent with books, neither in boys nor in girls, however, the limited sample size has to be considered. Conclusion Child health (and behavior) of first grade school children is possibly impacted by the COVID-19 pandemic with adverse consequences possibly differing by gender.